Effects of mass imbalance on metal-insulator transitions in the ionic Hubbard model - Nguyen, Thi Hai Yen; Hoang, Anh Tuan; Le, Duc Anh (Communications in Physics, 2025)
We investigated the effects of mass imbalance on the metal-insulator phase diagram in the half-filled ionic Hubbard model using dynamical mean field theory (DMFT) and the equations of motion (EOM) method to solve the impurity problem. Our results show that the band insulator region changes less significantly compared to the Mott insulator region, while the metallic region shrinks as the mass imbalance increases. Additionally, the staggered charge density was calculated and analyzed for various values of mass imbalance, providing further insight into the critical Coulomb interaction values that govern phase transitions.